FACTORS RELATED TO THE NUTRITIONAL STATUS OF TODDLERS AGED 2-6 YEARS IN PUCANGRO VILLAGE, GUDO DISTRICT, JOMBANG REGENCY - Mauluvya, Ayank Illa; Kusyani, Asri; Hamid, Hamid (WELL BEING, 2019)
Nutrition is an important factor that determines the level of health and well-being of humans where the level of optimal nutritional status will be achieved if the optimal nutritional needs are fulfilled. Nutrition in toddlers is influenced by several factors, namely mother's age, mother's occupation, mother's nutritional knowledge, number of children and family economy. The purpose of this study is to analyze the factors related to the nutritional status of toddlers under five. This research uses correlation analytic design with cross sectional approach. The sample used was 59 respondents. The sampling technique used was purposive sampling. Data collection used a questionnaire. The results obtained are that the mother's knowledge of the nutritional status of toddlers was as many as 54 people (91.5%) with a good nutritional status of toddlers. Based on the statistical tests, there is a correlation between mother’s knowledge and nutritional status of toddlers under five in Pucangro Village, Gudo District, Jombang Regency with p = value (0.022) <(α: 0.05). There is no relationship between mother's age and nutritional status of toddlers under five with value of p = 0.431> α: 0.05, no relationship between mother's occupation and nutritional status of toddlers under five with a value of p = 0.405> α: 0.05, no relationship between the number of children with nutritional status of toddlers with p = 0.694> α: 0.05, and no economic relationship with the nutritional status of toddlers with p = 0.188> α: 0.05. The factors related to the nutritional status of toddlers under five must be considered such as mother's age, mother's occupation, number of children, family economy and mother's knowledge, in Pucangro Village, Gudo District, Jombang Regency, 54 people have good knowledge so that they can achieve good nutritional status. Keywords: Nutrition Status, Toddler